Marketing plan to strengthen the commercialization of panela in the Santa Rosa Association - Quiroz-Calampa, Leidy (2024)
The growing demand for organic products positions panela as a sustainable alternative. This study aims to develop a marketing plan to optimize its commercialization in the Santa Rosa Producers Association (APROSAR), working with the 15 members through a census approach and a descriptive-propositive design. Data were obtained through surveys with high reliability (Cronbach's alpha = 0.934). The results showed that 53.3% of the members are men and 46.7% are women, with ages predominantly between 26 and 40 years. The majority had secondary education (93.4%) and only 6.7% had higher education. Deficiencies were identified in the use of emerging technologies and digital platforms, which limits the brand's visibility in the market. The SWOT and PESTEL analysis revealed opportunities to promote panela as an organic product and strengthen the digital presence through the use of social networks and websites. A marketing plan was designed suggesting product diversification and participation in trade fairs. The implementation of the plan will enable APROSAR to overcome its weaknesses, improve its competitiveness and lay the foundations for long-term sustainable growth.